SUPREME COURT DECISIONS ON PUBLIC INFORMATION AND PERSONAL DATA PROTECTION - Brierly Napitupulu (Faculty of Law, Universitas Lampung, 2022)
The information disclosure issue to the public prompted the Supreme Court to issue a Regulation in the form of a Decision of the Supreme Court concerning Information Disclosure in Courts, which was supplemented by a Decision of the Supreme Court concerning Guidelines for Information Services in Courts. This decision resulted in the existence of the Supreme Court Decision Directory that allows the public free access to a copy of each case's entire decision. Meanwhile, the Criminal Procedure Code limits the distribution of copies of decisions in cases where not everyone can obtain a court decision. The objective of this research is to know how the legal protection of the parties' personal data in the Directory of Decisions of the Supreme Court, especially in criminal cases. Data analysis was performed using legal theory and related legislation, with doctrinal research, concept, and statutory approach methods. The conclusions obtained by the Supreme Court Decision Directory have not fully provided legal protection for the Personal Data of the Parties, especially the Defendant. The KMA SK, which is the technical guideline for information disclosure in court, does not mention Defendant's privacy rights and also the privacy rights of third parties.